ผลของการเรียนการสอนฟุตบอลโดยใช้โปรแกรมการฝึกแรงต้านที่มีต่อพลังกล้ามเนื้อขาของนักกีฬาฟุตบอลระดับอุดมศึกษา - ไอยย์ศรัย พีรภาพรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this research were to study and compare the effects of football instruction using a resistance training program on the power of leg muscles of higher education football players. The subjects were 40 football players from NakhonRatchasimaRajabhat University. They were then assigned into 2 groups by matching group method and divided into 20 subjects in each group; the control group was trained by using regular training program while the experimental group was trained by using a resistance training program. Both groups were trained for 3 days a week for a period of 8 weeks. The levels of power of leg muscles in bothgroups were tested before training, after training 4 weeks and 8 weeks. The obtained data were analyzed in terms of means and standard deviations, one-way analysis of variance with repeated measures and multiple comparison by LSD were also employed for statistical significance at .05 level. The results were as follows: 1. After 4 weeks of experiment, the power of leg muscles in the experimental group was significantly higher than before experiment at .05 level. 2. After 8 weeks of experiment, the power of leg muscles in the experimental group was significantly higher than after 4 weeks of experiment at .05 level. 3. After 8 weeks of experiment, the power of leg muscles in the experimental group was significantly higher than before experiment at .05 level. 4. After 4 weeks of experiment, the power of leg muscles in the experimental group and the control was not significantly at .05 level. 5. After 8 weeks of experiment, the power of leg muscles in the experimental group was significantly higher than the control group at .05 level.